Radegund: The Trials and Triumphs of a Merovingian Queen. By Erin T. Dailey. New York, NY: Oxford University Press, 2023. ISBN 978-0-197-69920-1. 232 pp - Birgit Kynast (Royal Studies Journal)
Radegund: The Trials and Triumphs of a Merovingian Queen. By Erin T. Dailey. New York, NY: Oxford University Press, 2023. ISBN 978-0-197-69920-1. 232 pp